A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae) - Botero-Trujillo, Ricardo; González-Gómez, Julio C.; Valenzuela-Rojas, Juan C.; García, Luis F. (Zootaxa, 2017)
We describe a new scorpion species in the troglomorphic genus Troglotayosicus Lourenço, 1981 from Colombia. Troglotayosicus meijdeni sp. nov. inhabits the forest leaf litter at Rivera municipality, on the western slope of the Eastern Andes. The male of the new species remains unknown; however, this species can be distinguished from other species in the genus by the female (and juvenile) morphology. The type locality of T. meijdeni sp. nov. represents the northernmost known record for a population of Troglotayosicus, further extending the known limits of distribution of this genus, and shedding more light on the distributional range of this group of scorpions in northwestern South America. With this description, the number of known species of Troglotayosicus is raised to four; three of them are endogean species living in forested areas in the Andean region of Colombia, whereas one is a hypogean species from a cave in Ecuadorian Amazonia.